(untitled) (Applied Biological Research, 2025)
Transient pore formation in lipid membranes plays a critical role in diverse biological and synthetic processes. Understanding the molecular transport mechanism through these membrane pores is a key step in the optimization of drug release and membrane integrity regulation. In this study, we investigated molecular transport through nanopores formed in the membrane of Giant Unilamellar Vesicles (GUVs) using finite element simulation in COMSOL Multiphysics. We explored the impact of nanopore diameter (16–60 nm) and fluorescent probe size (RSE 0.74–5.00 nm) on molecular transport. Using Fick’s law of diffusion and the Stokes-Einstein equation, we calculated leakage rate constants (kleak) for various fluorescent probe sizes. Simulations revealed that larger nanopores significantly increased leakage rates, whereas increasing probe size led to slower leakage. Additionally, larger suspension areas accelerated molecular clearance from the vesicle, amplifying overall flux. The model was validated against experimental data on magainin 2-induced pores, showing strong agreement and confirming the accuracy of our approach. These findings provide insight into nanopore-mediated transport and offer a predictive framework for designing membrane-permeabilizing systems in synthetic biology and drug delivery applications.